Obesity Awareness and Nutrition Behavior of Children in Uşak Province, Republic of Turkey - Akil, Mustafa; Top, Elif (The Food and Nutrition Society of Indonesia in collaboration with the Department of Community Nutrition, IPB University, 2019)
This study aimed to investigate the correlation between the awareness of children about obesity and their nutritional behaviors. Obesity Awareness Scale (OAS) and the Food Behavior Scale (FBS) were utilized for the data collection in the present study. The subjects were 699 male and female school children. Analyisis showed a significant correlation between the sub-dimensions of OAS and the total scores of FBS (p<0.05). There were significant differences on levels of OAS and FBS depending on educational status (p<0.05). The total score of FBS was also differ significantly between the healthy participants and the overweight ones (p<0.05). The results showed that there is a positive correlation between the nutritional behaviors and obesity awareness; being or not being engaged in sports does not have an effect in the study subject's obesity awareness and nutrition behaviour; the nutritional behaviours and obesity awareness are depending on the educational level of the mother and the father and the subjects who have good nutritional behaviors, also have normal BMI (Body Mass Index).